2019
DOI: 10.4269/ajtmh.18-0731
|View full text |Cite
|
Sign up to set email alerts
|

Association of a PD-L2 Gene Polymorphism with Chronic Lymphatic Filariasis in a South Indian Cohort

Abstract: Lymphatic filariasis (LF) is a parasitic infection, caused by three closely related nematodes, namely Wuchereria bancrofti, Brugia malayi, and Brugia timori. Previously, we have shown that lysate from B. malayi microfilariae induces the expression of interleukin (IL)-10 and programmed death-ligand (PD-L) 1 on monocytes, which lead to inhibition of CD4 + T-cell responses. In this study, we investigated associations of IL-10 and programmed cell death (PD)-1 pathway gene polymorphisms with clinical manifestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…36 For patients with chronic lymphatic filariasis, rs4143815 showed no difference in genotype distribution between patients and healthy controls in the south Indian population. 37 In the present study, the frequencies of CC genotype and C allele at the rs4143815 locus were found to be significantly lower in SLE patients than in healthy controls, suggesting that the rs4143815 polymorphism is associated with lower risk of SLE in the Chinese Han population and may be a protective factor for SLE development. This study also showed that GA genotype at the rs822339 locus may be associated with risk of developing SLE, and frequency of GA genotype was higher in SLE patients than in healthy controls, suggesting that the rs822339 GG genotype may be negatively associated with the risk of developing SLE.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…36 For patients with chronic lymphatic filariasis, rs4143815 showed no difference in genotype distribution between patients and healthy controls in the south Indian population. 37 In the present study, the frequencies of CC genotype and C allele at the rs4143815 locus were found to be significantly lower in SLE patients than in healthy controls, suggesting that the rs4143815 polymorphism is associated with lower risk of SLE in the Chinese Han population and may be a protective factor for SLE development. This study also showed that GA genotype at the rs822339 locus may be associated with risk of developing SLE, and frequency of GA genotype was higher in SLE patients than in healthy controls, suggesting that the rs822339 GG genotype may be negatively associated with the risk of developing SLE.…”
Section: Discussionsupporting
confidence: 48%
“…In a Polish study of non‐small cell lung cancer, a higher frequency of CC genotype at the rs4143815 locus in the patient group than in healthy controls was noted (OR = 2.31) 36 . For patients with chronic lymphatic filariasis, rs4143815 showed no difference in genotype distribution between patients and healthy controls in the south Indian population 37 . In the present study, the frequencies of CC genotype and C allele at the rs4143815 locus were found to be significantly lower in SLE patients than in healthy controls, suggesting that the rs4143815 polymorphism is associated with lower risk of SLE in the Chinese Han population and may be a protective factor for SLE development.…”
Section: Discussionmentioning
confidence: 95%
“…Among the 12 PDCD1LG2 SNPs, the clinical significance of rs7854413 was the most commonly reported in the previous literatures. A cohort study in south India reported that patients with the PDCD1LG2 SNP rs7854413 and lymphatic filariasis infection were susceptible to chronic lymphatic pathologies (40), and rs7854413 polymorphism was related to advanced fibrosis and development of hepatocellular carcinoma from patient with non-alcoholic steatohepatitis (41). Notably, rs7854413 was also associated with recurrence in patients with early-stage NSCLC (42).…”
Section: Discussionmentioning
confidence: 99%
“…The variability of prevalence and clinical outcomes of lymphatic filariasis are affected by socioeconomic status, personal activities, age, gender and host genetics [2,3,4]. The polymorphisms of host defense pathway genes, including MBL , VEGF , HLA , TLR , PDL-1i and IL-10RB are associated with susceptibility and clinical status of the disease [5,6,7,8,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the association of polymorphisms of host defense pathway genes with susceptibility and clinical outcomes of bancroftian filariasis (BF). Polymorphisms of mannose-binding lectin ( MBL ), vascular endothelial growth factor ( VEGF ), human leukocyte antigen ( HLA ), toll-like receptor ( TLR ), programmed cell death-1 ( PDL-1 ), interleukin-10 ( IL-10RB ) and chitotriosidase ( CHIT1 ) increase susceptibility to BF [5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%